My trip moment - Doh, Shu Ing (Faculty of Civil Engineering & Earth Resources, 2018)
BEIJING-August 2018, International Summer School of Sustainable Infrastructure (1-16 August 2018) is the annual event organised by Beijing JiaoTong University. This program was organized as part of the summer school activities including a public lecture, laboratory visit, site visit and industrial visit.